A new species of Sessilogoga (Crustacea: Thecostraca: Ascothoracida) parasitic in an antipatharian from Bidong Island, Malaysia - Kolbasov, Gregory A.; Savchenko, Alexandra S. (Zootaxa, 2024)
More than 30 specimens of both sexes of a new endoparasitic ascothoracidan, described herein as Sessilogoga perfuga sp. nov. in the family Synagogidae, were found infecting the colonies of the antipatharian Antipathes cf. curvata at 25–29 m depth in the vicinity of Bidong Island, Kuala Nerus District, Malaysia. Several individuals were observed alive and photographs and videos were taken of parasites both inside the host and after they have left the coral. Scanning electron microscopy (SEM) was used supplementing light microscopy examinations to study external morphology of both sexes at the ultrastructural level. Carapace ornamentation, armature of antennules, telson and furcal rami, as well as fine details of the mouthparts were studied with SEM. All three known species of the genus Sessilogoga share several synapomorphies, probably connected with their endoparasitic way of life, that distinguish them from closely related Synagoga and Waginella: (i) a smaller frontal filament complex; (ii) the absence of epaulets on thoracomere 6; (iii) fewer setae on the proximal antennular segments; and (iv) more seminal receptacles in any given pair of thoracopods. Here we discuss characters that can be used for identification of Sessilogoga species: (i) the armament of antennules; (ii) the form of the tips of maxillules; (iii) setation of thoracopods; (iv) number of seminal receptacles; (v) structure of telsonic spines; and (vi) length/height ratio of furcal rami. Molecular gene sequences of CO1 marker of the new species are provided for future phylogenetic analysis of the Ascothoracida.